Effect of Al-doping on the thermoelectric properties of CZTS thin film grown by sol-gel method. (1st April 2022) - Ashfaq, Arslan; Jacob, Jolly; Amami, Mongi; Al-Harbi, F.F.; Ali, A.; Mahmood, K.; Rehman, U.; Amin, N.; Ikram, S.; Akbar, S. Tahir; Hussain, S.
Abstract: In this paper, thermoelectric (TE) properties of sol-gel grown Cu2-x Alx ZnSnS4 thin films were investigated using Seebeck data. Several thermoelectric parameters such as Seebeck coefficient (71–110 μV/ ° C), electrical conductivity (29.4–36.98 S/cm) and power factor (1.48 × 10 −5 - 4.29 × 10 −5 Wm −1 C −2 ) were improved with the concentration of Al atoms. The improvement in thermo-electrical properties is linked to the transfer of the electron density to the Cu and Sn atoms, which generated the copper and tin based secondary phases. The formation of secondary phases with the addition of Al atoms in the host CZTS structure is resulted in the simultaneous improvement of Seebeck coefficient and electrical conductivity due to energy filtering effect. Additional measurements such as X-ray Diffraction, Raman Spectroscopy, and Scanning Electron Microscopy were performed to back up this argument. The formation of extra secondary phases with increasing Al atoms concentration was justified by XRD and Raman data. SEM images revealed the irregular formation of grain size having micro and nanoscale. Highlights: Growth of CZTS by sol-gel method. Effect of Al doping on various properties. XRD, Raman measurements are used for structure verification. Thermoelectric properties improved with Al doping up to a limit.